Emissions from several in-use ships tested by portable emission measurement system. (1st April 2016) - Peng, Zihang; Ge, Yunshan; Tan, Jianwei; Fu, Mingliang; Wang, Xin; Chen, Ming; Yin, Hang; Ji, Zhe
Abstract: Seven ships were tested using portable emission measurement system. Particles from three ships were sampled using quartz-filters and analyzed using Thermal/Optical Carbon Analyzer and GC–MS. The emission factors of CO, HC, NOx and PM are 11.00–84.60 g/kg, 22.75–98.88 g/kg, 0.72–5.83 g/kg and 0.15–9.53 g/kg, respectively. In most cases, the ships emit larger quantity of pollutants during cruising. For particle number, the majority is formed in the nucleation mode. The nucleation mode and the accumulation mode from ships during maneuvering increase by 2.63 and 3.52 times respectively, compared with those from ships during cruising. Particle mass is dominated by the accumulation mode and the coarse mode. Analysis of the samples shows that OC is the major composition of carbonaceous particle, whose mass fraction is 0.52–0.88. The emission factors of OC and EC are 0.29–1.44 g/kg and 0.04–0.64 g/kg, respectively. Most of the particle-phase PAHs are medium molecular weight PAHs, while high molecular weight PAHs are seldom observed. Highlights: The emission factors of CO, NOx, HC, PM, OC, EC & particle-phase PAHs are provided. Both the nucleation mode and the accumulation mode are higher when the ship is maneuvering. More OC and EC are generated in the maneuvering mode. PAHs from ships majorly compose of MMW PAHs.